Ser Cepparello e il «giudicio» degli uomini (ENTHYMEMA, 2013)
This paper proposes a hypothesis on the first novel of Boccacio’s Decameron and, in particular, on its protagonist. It proceeds then by reflecting upon Boccaccio’s axiological system, focusing on the oeuvre’s narrative structure.